Apprenticeship, Vocationalism and Opposing VET-Reform Trends in Europe - Gonon, Philipp [Verfasser] (My University, 2008)
"Considering the international prominence of 'work-based learning' or the concept of 'situational learning', as well as endeavours to strengthen or reintroduce apprenticeship models characterized by their proximity to the world of work and their practical relevance, it seems that there is a clash of two rather oppositional tendencies in the reform discussions. The present contribution aims to provide a historical view of these opposing trends. Education, and in particular professional training, oscillates between immediate professional requirements and more abstract, long-term demands. This discussion is to be found in the theory of education as well as in the development of education institutions. Europe-wide, it seems likely that a mixture of curricular and institutional practices to prevail, thereby doing justice to the hybridity of the world of work and the youths' different abilities." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 1 Curricula & Lehrpläne; L 2.1 Lernformen; T 2.1 Bildungstheorien; T 2.2 Lerntheorien; I 2.2 Europa; Berufsausbildung; Reform; Ausbildungsinhalt; Bildungstheorie; Lerntheorie; Beruflichkeit; Lernen am Arbeitsplatz; Europa